Appropriate ICT as a Tool to Increase Effectiveness in ICT4D: Theoretical considerations and illustrating cases - and Reijswoud, Victor van (The Electronic Journal of Information Systems in Developing Countries, 2009)
The need to bridge the digital divide is no longer a point of discussion and therefore focus has shifted to the design and implementation of programs that have the potential to close the information and knowledge gap between the developing and developed nations. Unfortunately, the majority of these programs are small and mimic what has been successful in the developed world. It has become increasingly clear that these successes do not necessarily translate well in the context of developing nations. This paper develops the hypothesis that Information and Communication Technology (ICT) projects in developing countries will become successful only when they are adapted to local conditions. The general concept of Appropriate Technology (AT) will be explored for the field of ICT. AT has already been embraced by fields like architecture, building technology and agriculture, but has not yet been rooted in ICT. The paper proposes a preliminary theory of Appropriate ICT along the lines of existing theories in AT and System development. The theory identifies Appropriate Technology principles at three levels: hardware, software and ICT change management. By means of real life mini cases in the ICT for Development context in Africa, the guiding principles for Appropriate ICT are illustrated. The paper will conclude with an agenda for further research in the three identified levels. The research agenda targets academia, governments, NGO's and industry.
Keywords: IMPORTANT